Statin drugs enhance responses to immune checkpoint blockade in head and neck cancer models - Chrystal Paulos; Gregory B Lesinski; Zachary S Buchwald; Nabil F Saba; Vikash Kansal; Andre J Burnham; Brendan L C Kinney; Nicole C Schmitt (Journal for ImmunoTherapy of Cancer)
Background Anti-PD-1 immune checkpoint blockade is approved for first-line treatment of recurrent/metastatic head and neck squamous cell carcinoma (HNSCC), but few patients respond. Statin drugs (HMG-CoA reductase inhibitors) are associated with superior survival in several cancer types, including HNSCC. Emerging data suggest that manipulation of cholesterol may enhance some aspects of antitumor immunity.Methods We used syngeneic murine models (mouse oral cancer, MOC1 and TC-1) to investigate our hypothesis that a subset of statin drugs would enhance antitumor immunity and delay tumor growth.Results Using an ex vivo coculture assay of murine cancer cells and tumor infiltrating lymphocytes, we discovered that all seven statin drugs inhibited tumor cell proliferation. Simvastatin and lovastatin also enhanced T-cell killing of tumor cells. In mice, daily oral simvastatin or lovastatin enhanced tumor control and extended survival when combined with PD-1 blockade, with rejection of MOC1 tumors in 30% of mice treated with lovastatin plus anti-PD-1. Results from flow cytometry of tumors and tumor-draining lymph nodes suggested T cell activation and shifts from M2 to M1 macrophage predominance as potential mechanisms of combination therapy.Conclusions These results suggest that statins deserve further study as well-tolerated, inexpensive drugs that may enhance responses to PD-1 checkpoint blockade and other immunotherapies for HNSCC.